2022
DOI: 10.1177/09622802221129051
|View full text |Cite
|
Sign up to set email alerts
|

Online control of the False Discovery Rate in group-sequential platform trials

Abstract: When testing multiple hypotheses, a suitable error rate should be controlled even in exploratory trials. Conventional methods to control the False Discovery Rate assume that all p-values are available at the time point of test decision. In platform trials, however, treatment arms enter and leave the trial at different times during its conduct. Therefore, the actual number of treatments and hypothesis tests is not fixed in advance and hypotheses are not tested at once, but sequentially. Recently, for such a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For further discussion and proposals for this setting, we refer the interested reader to Zrnic et al, 23 who proposed a framework for asynchronous online testing. As well, recent work by Zehetmayer et al 36 shows how to use LOND specifically for group-sequential platform trials.…”
Section: Discussionmentioning
confidence: 99%
“…For further discussion and proposals for this setting, we refer the interested reader to Zrnic et al, 23 who proposed a framework for asynchronous online testing. As well, recent work by Zehetmayer et al 36 shows how to use LOND specifically for group-sequential platform trials.…”
Section: Discussionmentioning
confidence: 99%
“…Stallard et al, 7 Collignon et al 9 ) and alternatives (like FDR -control) have been suggested rather recently (e.g. Zehetmayer et al, 25 Robertson et al 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, from a public health perspective, quantifying the risk of false positive conclusions at the platform level is essential and can be achieved with tailored, so called online multiple testing procedures. 24 , 25 …”
Section: Improving Efficiency Through Adaptive Clinical Trial Designmentioning
confidence: 99%